2022
DOI: 10.1038/s41390-022-02309-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on children’s sleep habits: an ECHO study

Abstract: Background Sleep in childhood is affected by behavioral, environmental, and parental factors. We propose that these factors were altered during the COVID-19 pandemic. This study investigates sleep habit changes during the pandemic in 528 children 4–12 years old in the US, leveraging data from the Environmental Influences on Child Health Outcomes (ECHO) Program. Methods Data collection occurred in July 2019–March 2020 (pre-pandemic) and two pandemic periods: December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Although intrinsic factors regulate sleep, extrinsic factors are essential in determining sleep duration, timing, and quality. Behavioral factors (e.g., screen time, PA, bedtime routine), physical and environmental factors (e.g., light and noise exposure), and parental factors (e.g., parental child attachment, parental education, parental stress) all affect the sleep health of children [ 50 ]. The recommended sleep amount for school-age children of 6–13 years of The Sleep Foundation Organization is about 9–11 h per night [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although intrinsic factors regulate sleep, extrinsic factors are essential in determining sleep duration, timing, and quality. Behavioral factors (e.g., screen time, PA, bedtime routine), physical and environmental factors (e.g., light and noise exposure), and parental factors (e.g., parental child attachment, parental education, parental stress) all affect the sleep health of children [ 50 ]. The recommended sleep amount for school-age children of 6–13 years of The Sleep Foundation Organization is about 9–11 h per night [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in outdoor activities on one side and the increased exposure to light from screens and stress on the other may have been crucial [55][56][57]. In other studies, no overall change in sleep duration was found, despite a delay in bedtime and waketime, with a likely protective effect of parental education [58]. By contrast, some authors highlighted improved sleep quality in adolescents and young adults due to the more flexible virtual learning programs and remote working [59].…”
Section: Social Habits and Emotional Well-beingmentioning
confidence: 92%
“…In 2021 in the United States, only about 36% of people had an annual household income greater than $100,000 (Semega & Kollar, 2022). In addition, we lacked data about race and ethnicity from most of our sample, so we were unable to test for cultural differences that can impact infant sleep (e.g., Ash et al, 2019;Giannotti & Cortesi, 2009;Lucchini et al, 2022). One additional limitation is that we are unsure why some infants were missing sleep data for certain nights.…”
Section: Strengths and Limitationsmentioning
confidence: 99%